(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Il migrante e il suo Dio: prove di identificazione e input di integrazione? - 2. L’identità (anche religiosa) della persona migrante. Dalle politiche discriminatrici all’integrazione civica nel modello di accoglienza italiano. Profili critici - 3. Una (prima e utopica) conclusione: la ridefinizione dell’ordine costituente a partire dall’Altro. The (religious) identity of the migrant person in the reception system, between security drifts and civic integration policies. Brief considerations. ABSTRACT: The essay takes into consideration some general profiles relating to the issue of immigration. Particular attention is paid to the critical issues that can be found in the context of the reception system in Italy that compromise the migrant’s right to religious identity.